Ignored role of polyphenol in boosting reactive oxygen species generation for polyphenol/chemodynamic combination therapy. (December 2022) - Mao, Huijia; Wen, Yangyang; Yu, Yonghui; Li, Hongyan; Wang, Jing; Sun, Baoguo
Abstract: Chemodynamic therapy (CDT) is a promising tumor-specific treatment, but still suffering insufficient reactive oxygen species (ROS) levels due to its limited efficacy of Fenton/Fenton-like reaction. Polyphenol, as a natural reductant, has been applied to promote the efficacy of Fenton/Fenton-like reactions; however, its intrinsic pro-apoptosis effects was ignored. Herein, a novel CDT/polyphenol-combined strategy was designed, based on Avenanthramide C-loaded dendritic mesoporous silica (DMSN)-Au/Fe3 O4 nanoplatforms with folic acid modification for tumor-site targeting. For the first time, we showed that the nanocomplex (DMSNAF-AVC-FA) induced ROS production in the cytoplasm via Au/Fe3 O4 -mediated Fenton reactions and externally damaged the mitochondrial membrane; simultaneously, the resultant increased mitochondrial membrane permeability can facilitate the migration of AVC into mitochondrial, targeting the DDX3 pathway and impairing the electron transport chain (ETC) complexes, which significantly boosted the endogenous ROS levels inside the mitochondrial. Under the elevated oxidative stress level via both intra- and extra-mitochondrial ROS production, the maximum mitochondrial membrane permeability was achieved by up-regulation of Bax/Bcl-2, and thereby led to massive release of Cytochrome C and maximum tumor cell apoptosis via Caspase-3 pathway. As a result, the as-designed strategy achieved synergistic cytotoxicity to 4T1 tumor cells with the cell apoptosis rate of 99.12% in vitro and the tumor growth inhibition rate of 63.3% in vivo, while very minor cytotoxicity to normal cells with cell viability of 95.4%. This work evidenced that natural bioactive compounds are powerful for synergistically boosting ROS level, providing new insight for accelerating the clinical conversion progress of CDT with minimal side effects. Graphical abstract: Image 1 Highlights: A novel CDT/polyphenol-combined nanoplatform, DMSNAF-AVC-FA was designed. DMSNAF-AVC-FA induced ROS production and externally damaged mitochondrial membrane. DMSNAF-AVC-FA facilitated AVC targeting the DDX3 pathway and impairing ETC complexes. DMSNAF-AVC-FA achieved synergistic antitumor efficacy both in vitro and in vivo .